(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Philosophical discourse relies heavily on precise and nuanced terminology to convey complex and abstract ideas. The formation of these terms is deeply rooted in semantic processes, which shape and define their meanings. This thesis explores the semantic methods by which philosophical terms are formed in the English language, focusing on the ways in which meaning is constructed, interpreted, and communicated. By examining the semantic structures that underpin philosophical terminology, this research aims to uncover the linguistic mechanisms that facilitate the expression of philosophical thought. This study not only contributes to our understanding of semantic theory but also highlights the crucial role of language in shaping philosophical inquiry.